2020
DOI: 10.1101/2020.10.29.20217059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine mapping of the HLA locus in Parkinson’s disease in Europeans

Abstract: Objective: Previous studies suggested a role for the immune system in Parkinson disease (PD), and one of the hits in recent genome-wide association studies (GWASs) of PD is within the human leukocyte antigen (HLA) locus. Several associations of different HLA genes have been suggested, yet it is not clear which associations are relevant for PD. Methods: We performed a thorough analysis of the HLA locus in 13,770 PD patients, 20,214 proxy-cases and 490,861 controls of European origin. We used GWAS data to impute… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…We identified a spatial eQTL between rs504594 and HLA-DRB1 in both the foetal cortex and adult brain (including cortex and SN), implicating this regulatory eQTLgene connection in both the neurodevelopment and neurodegenerative stages of PD. Interestingly, rs504594 (previous ID: rs112485776) was recently validated in a SNP-level meta-analysis (OR = 0.87), with results displaying no residual HLA effect in adults after adjusting for the SNP 75 . Instead, three amino acid polymorphisms within the HLA-DRB1 gene were identified as drivers of the association between the HLA region and PD risk 75 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We identified a spatial eQTL between rs504594 and HLA-DRB1 in both the foetal cortex and adult brain (including cortex and SN), implicating this regulatory eQTLgene connection in both the neurodevelopment and neurodegenerative stages of PD. Interestingly, rs504594 (previous ID: rs112485776) was recently validated in a SNP-level meta-analysis (OR = 0.87), with results displaying no residual HLA effect in adults after adjusting for the SNP 75 . Instead, three amino acid polymorphisms within the HLA-DRB1 gene were identified as drivers of the association between the HLA region and PD risk 75 .…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, rs504594 (previous ID: rs112485776) was recently validated in a SNP-level meta-analysis (OR = 0.87), with results displaying no residual HLA effect in adults after adjusting for the SNP 75 . Instead, three amino acid polymorphisms within the HLA-DRB1 gene were identified as drivers of the association between the HLA region and PD risk 75 . We agree that the impacts of rs504594 are contingent upon the HLA-DRB1 allele -both in terms of regulation and protein sequence.…”
Section: Discussionmentioning
confidence: 98%
“…The PD samples included in the analysis are part of the following datasets for which the phenotyping, genotyping and quality control has been described elsewhere 10,18,19,26,29,66 The samples assessed for AD and Lewy-body neuropathology included genetic data from the Rush Religious Orders Study and Memory and Aging Project (ROSMAP) 67 and from the Alzheimer"s Disease Center (ADC) cohorts 1 to 7 parts of the ADGC 68 , and Extended Data Figure 6. HLA binding predictions for PHF6.…”
Section: Methods Onlinementioning
confidence: 99%
“…Two recent large studies in PD 18,19 have shown that the HLA signal in PD is best summarized by a primary protective effect of HLA-DRB1 amino acids 13H and 33H shared by all HLA-DRB1*04 subtypes. HLA-DRB1 amino acids 11V also showed a strong association; this amino acid is shared by HLA-DRB1*04 and HLA-DRB1*10:01, a subtype not associated with the disease.…”
Section: Colocalization Of Hla Snp Signals In Ad and Pd Across Ethnic Groupsmentioning
confidence: 99%
See 1 more Smart Citation